Electrochemical Water Oxidation at Iron(III) Oxide Electrodes Controlled Nanostructuring as Key for Enhanced Water Oxidation Efficiency - Haschke, Sandra (BestMasters,, 2015)
Sandra Haschke presents a strategy to enhance the Fe2O3 electrode performance by controlled nanostructuring of the catalyst surface, based on anodized aluminum oxide coated by means of atomic layer deposition. Furthermore, she investigates the influence of underlying conductive layers and post-deposition annealing on the electrode performance and the associated changes in morphology and chemical composition. Exploiting all effects combined delivers an increase in steady-state water oxidation throughput by a factor of 2.5 with respect to planar electrodes.  Contents Preparation of Nanostructured Fe2O3 Electrodes Chemical and Structural Properties of Nanoporous Catalyst Electrodes Modification of Nanostructured Fe2O3 Electrodes by Means of Post-Deposition Annealing Improvement of Electrode Performance by Surface Area Enhancement  Target Groups Researchers and students in the fields of electrochemistry, materials sciences and physical chemistry Practitioners in these areas  The Author Sandra Haschke obtained her Master's degree in chemistry at the Friedrich-Alexander University Erlangen-Nürnberg under the supervision of Prof. Dr. Julien Bachmann where she will continue with her PhD thesis.